Nutrition Education Program and Physical Activity Improve the Adherence to the Mediterranean Diet: Impact on Inflammatory Biomarker Levels in Healthy Adolescents From the DIMENU Longitudinal Study - Morelli, Catia; Avolio, Ennio; Galluccio, Angelo; Caparello, Giovanna; Manes, Emanuele; Ferraro, Simona; Caruso, Antonella; De Rose, Daniela; Barone, Ines; Adornetto, Carlo; Greco, Gianluigi; Catalano, Stefania; et al. (Frontiers in Nutrition, 2021)
Adherence to Mediterranean Diet (MD) and Physical Activity (PA) in adolescence represent powerful indicators of healthy lifestyles in adulthood. The aim of this longitudinal study was to investigate the impact of nutrition education program (NEP) on the adherence to the MD and on the inflammatory status in healthy adolescents, who perform PA at different levels. As a part of the DIMENU study, 85 adolescents (aged 14-17 years) participated to the nutrition education sessions provided by a team of nutritionists and endocrinologists at T0. All participants underwent to anthropometric measures, bio-impedentiometric analysis and measurements of inflammatory biomarkers such as C-reactive protein (CRP) and Ferritin levels. Data were collected at baseline (T0) and six months after NEP (T1). To assess the adherence to the MD and dietary composition we used KIDMED score. In our adolescents, we found an average MD adherence which was strongly increased at T1 compared with T0 (T0: 6.03±2.33 vs T1: 6.96±2.03, p=0.002), with an enhanced percentage of adolescents with optimal (≥8 score) MD adherence over the study period (T0: 24.71% vs T1: 43.52%, p=0.015). Interestingly, in linear mixed-effects models, we found that NEP and vigorous intensity PA levels independently influenced KIDMED score (β=0.868, p<0.0001 and β=1.567, p=0.009, respectively). Evaluating the serum inflammatory biomarkers in our population at both T0 and T1, serum Ferritin and CRP levels were significantly reduced (1.94 ± 3.07 vs 1.53 ± 2.76, p=0.028 and 50.66 ± 33.90 vs 17.79 ± 16.75, p<0.001). We also observed in linear mixed-effects models that NEP negatively affected Ferritin and CRP (β=-14.763, p<0.001 and β=-0.714, p=0.02, respectively). Our results suggest the usefulness to promote healthy lifestyle, including nutritional education interventions and PA to improve MD adherence and to blunt the inflammatory status in adolescence as a strategy for the prevention of chronic non-communicable diseases over the entire lifespan.